2007
DOI: 10.1177/1043659606298613
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Congruent Care

Abstract: This article presents the 3-D puzzle model of culturally congruent care, defines the levels and constructs employed by this model, presents some assumptions, and lays out some basic propositions as a foundation for further work. There are many extant frameworks and theories of culture and cultural competence in nursing and health care; the model presented here draws heavily from prior work and is an attempt to present a synthesis of concepts and processes in a new way. The ideas presented here build particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 27 publications
1
66
0
1
Order By: Relevance
“…Three qualitative studies 41,42,44 discussed conflict related to the presence or absence of cultural congruence (defined as cultural diversity, awareness, sensitivity, and competence 49 ) at the level of the health care provider. In some instances, the cultural focus was socioeconomic status, as in a study of African American breast cancer patients who reported that class and education were important determinants in how providers treated them.…”
Section: Resultsmentioning
confidence: 99%
“…Three qualitative studies 41,42,44 discussed conflict related to the presence or absence of cultural congruence (defined as cultural diversity, awareness, sensitivity, and competence 49 ) at the level of the health care provider. In some instances, the cultural focus was socioeconomic status, as in a study of African American breast cancer patients who reported that class and education were important determinants in how providers treated them.…”
Section: Resultsmentioning
confidence: 99%
“…The four constructs include: (a) cultural diversity, which varies in quantity and quality across place and time and includes not only differences in race and ethnicity but also differences in language, religion, gender, sexual orientation, and socioeconomic class; (b) cultural awareness,which includes knowledge and recognition of the various factors that contribute to differences in and between groups; (c) cultural sensitivity, or attitudes about oneself and willingness to become more culturally knowledgeable and skillful; and (d) cultural competence behaviors, which involves a set of behaviors demonstrated in response to cultural diversity, awareness, and sensitivity (Schim et al, 2007). Schim and colleagues (2007) theorize that all four constructs are required, but are not individually sufficient to achieve culturally competent care.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, the development of cultural competence is an ongoing process that is informed by each cross-cultural encounter. The goal is not complete mastery of cultural competence, but rather matching provider competencies to meet the needs of specific populations and individuals who are the recipients of care (Schim et al, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Providers must work efficiently with the increasing number of patients, nurses, and health care team members whose ancestry reflects the multicultural complexion of contemporary society [15]. Key findings suggest that the ability to provide culturally competent care may be related to the nurse's knowledge and experience of psychological empowerment through a sense of meaning and competence in work.…”
Section: Resultsmentioning
confidence: 99%